2020
DOI: 10.1039/d0ra06428a
|View full text |Cite
|
Sign up to set email alerts
|

Elaborating piperazinyl-furopyrimidine based scaffolds as phosphoinositol-3-kinase enzyme alpha (PI3Kα) inhibitors to combat pancreatic cancer

Abstract: Phosphoinositol-3-kinase alpha (PI3K-α) enzyme inhibition to combat pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It has shown that the anti-proliferative activity of PI3Kα inhibitors was associated with cell cycle arrest [ 42 ]. Therefore, we examined the effects of 13k on cell cycle distribution.…”
Section: Resultsmentioning
confidence: 99%
“…It has shown that the anti-proliferative activity of PI3Kα inhibitors was associated with cell cycle arrest [ 42 ]. Therefore, we examined the effects of 13k on cell cycle distribution.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this represents the first synthesis of furans from oxime esters. 20 3-Cyanofurans are useful blocks for synthesizing complex molecules 21 and have shown interesting UV-absorbing properties; 22 thus, the development of novel protocols to access those heterocycles is an attractive goal. 23 When the transformation was applied to the formerly synthesized oximes 1 and others oxime esters, these molecules reacted with 2b to provide a wide range of furans in a more efficient fashion than was observed in the corresponding syntheses of pyrroles described above (Table 3).…”
Section: Resultsmentioning
confidence: 99%